The detection, diagnosis, and impact of cognitive impairment among inpatients aged 65 years and over in an Irish general hospital – a prospective observational study. (19th July 2017) - Power, Clodagh; Duffy, Richard; Bates, Helena; Healy, Mike; Gleeson, Petrina; Lawlor, Brian A.; Greene, Elaine
ABSTRACT: Background: The diagnosis of dementia remains inadequate, even within clinical settings. Data on rates and degree of impairment among inpatients are vital for service planning and the provision of appropriate patient care as Ireland's population ages. Methods: Every patient aged 65 years and over admitted over a two-week period was invited to participate. Those who met inclusion criteria were screened for delirium then underwent cognitive screening. Demographic, functional, and outcome data were obtained from medical records, participants, and family. Results: Consent to participate was obtained from 68.6% of the eligible population. Data for 143 patients were obtained. Mean age 78.1 years. 27.3% met criteria for dementia and 21% had mild cognitive impairment (MCI). Only 41% of those with dementia and 10% of those with MCI had a previously documented impairment. Between-group analysis showed differences in length of stay (p = 0.003), number of readmissions in 12 months (p = 0.036), and likelihood of returning home (p = 0.039) between the dementia and normal groups. MCI outcomes were similar to the normal group. No difference was seen for one-year mortality. Effects were less pronounced on multivariate analysis but continued to show a significant effect on length of stay even after controlling for demographics, personal and family history, and anxiety and depression screening scores. Patients with dementia remained in hospital 15.3 days longer (p = 0.047). A diagnosis is the single biggest contributing factor to length of stay in our regression model. Conclusions: Cognitive impairment is pervasive and under-recognized in the acute hospital and impacts negatively on patient outcomes.